PEMAHAMAN GURU PROPINSI JAWA TENGAH TERHADAP KEMAMPUAN MELIHAT DAN BERTANYA TENTANG REALITAS DALAM RANGKA PENERAPAN METODE PEMBELAJARAN ILMIAH - Harsono Harsono (Jurnal Pendidikan Ilmu Sosial, 2015)
The publication paper title is “ Elementary school Teachers Knowing for see and question in Central Java”. That is a part of researct publication. The reaserch location is Semarang, Demak, Kudus, and Pati teritorial. The problem statement of the paper are how long elementary school teachers knowed about capacity for reality see and questions. Instrumen of research is questionary, there are any question about elementary school teachers knowed about capacity for reality see and elementary school teachers knowed about capacity for reality questions. That is a quantitaive research and then survay research design. We get some information that level of capasity elementary school teachers knowed about capacity for reality see and questions are low. That is consistent with other research result, when we get a same kinds.